KEPADATAN DAN KEANEKARAGAMAN MEIOFAUNA DI PERAIRAN SUNGAI TALLO, MAKASSAR - Sisca Elviana (Universitas Musamus, Merauke, Papua, 2014)
Activity that produce waste around waters affects the physical condition of chemical and meiofauna waters is one of an organism that is affected .This research aims to analyze density and diversity meiofauna as well as to do with the quality of physics chemistry waters .This study was conducted in march-april 2014 , by taking sample in river waters tallo , south sulawesi province .Methods used is purposive random sampling .The results of observations with the help of microsoft office exel 2013 in river waters tallo found as many as 4 of taxa , with abundance of taxa most nematode on .Density meiofauna ranged between 0-14.55 ind / m3 while the diversity index ranges between 0-2.52 .The quality of waters that will support good life of the organism meiofauna so as to affect density and diversity meiofauna in waters.